Public Health Issues and Drug Abuse Research. Research Issues 30 - Metrotec Research Associates, Washington, DC.; Glynn, Thomas J.; Nelson, Jack E.; Metrotec Research Associates, Washington, DC. (Washington, D.C. : Distributed by ERIC Clearinghouse, 1982)
This volume, 30th of a series dealing with social and behavioral implications of human drug involvements, contains abstracts of literature concerning public health issues relevant to the drug field. Intended to provide drug researchers with a sampling of drug-relevant literature (published in English since 1970) across a number of public health areas, 77 articles are summarized and arranged alphabetically by author within these sections: general/historical issues; legal issues; ethical and social issues; research issues; treatment issues; single-drug issues; and international issues. The document also provides an extensive, supplementary bibiliography of additional readings, which were chosen through searches of major clearinghouses, databases, library collections, special bibliographies, current issues of newsletters and journals, and bibliographies provided by a peer review panel. Author and subject indexes are also included. (WAS)
Availability: Superintendent of Documents, U.S. Government Printing Office, Washington, DC 20402.
Sponsoring Agency: National Inst. on Drug Abuse (DHHS), Rockville, MD. Div. of Research.
Contract Number: NIDA-271-80-3720.
Researchers.
Microfiche.
Keywords: Drug Abuse; Drug Education; Drug Legislation; Drug Rehabilitation; Ethics; Public Health; Research Needs; Research Opportunities; Social Problems; Reference Materials, Bibliographies; Information Analyses